(untitled) (University Journal of Zoology, Rajshahi University, 2008)
The experiment was conducted to study the duration of different developmental stages of Oligonychus coffeae Nietner in six generations in different seasons of the year. The eggs of O. coffeae developed to adult within the shortest duration of 5.30±0.16 days at 30.28°C and 76.00% RH in June, but it took 12.91±0.21 days at 19.80°C and 75.41% RH in January. The highest temperature accelerated the developmental rate and reduced the duration of developmental stages. Temperature exerted significant effect on all the developmental stages of O. coffeae except deutonymph. But the relative humidity had no significant effect except deutonymph. Key words: Developmental stages, red spider mite, Oligonychus coffeae rose Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 71-72